Development of A Mobile-App-Based E-Assessment Oriented Towards Science Literacy For Prospective Science Teachers - Gunawan; Imam Bachtiar; Aliefman Hakim; Lovy Herayanti; Imran; Rahmatullah; Fathoroni; Lia Saptini Handriani (Postgraduate Program, University of Mataram, 2024)
This study aims to develop and test a mobile-app-based e-assessment oriented towards science literacy for prospective science teachers. The research and development (R&D) method with the 4D model was employed in this study. A multiple-choice test instrument with reasoning was developed to measure the science literacy skills of prospective science teachers. The instrument was validated by material experts and media experts to ensure its validity and reliability. The results showed that the developed mobile-app-based e-assessment is valid, reliable, and practical to use. Limited trials indicated that the application is effective in improving the science literacy of prospective science teachers. This research contributes to the development of innovative and effective technology-based assessment instruments to improve the quality of science education.